Corneal transplantation trends in France from 2004 to 2015: A 12-year review. Issue 5 (September 2018) - Bigan, Guillaume; Puyraveau, Marc; Saleh, Maher; Gain, Philippe; Martinache, Isabelle; Delbosc, Bernard; Gauthier, Anne-Sophie
Purpose: The aim of this study was to report the 12-year longitudinal trends in indication and corneal transplantation techniques in France from 2004 to 2015. Results: The records of all corneal transplantations performed from 2004 to 2015 in France were retrospectively reviewed. The patient indications and types of transplant performed were analyzed. A total of 46, 658 corneal transplantations were performed between 2004 and 2015, with 34, 187 (73.3%) penetrating keratoplasty and 10, 452 (22.4%) lamellar keratoplasty. The leading surgical indications were secondary endothelial failure (24.3%), keratoconus (18.8%), regraft (13.5%), and Fuchs endothelial corneal dystrophy (15.1%). Endothelial keratoplasty became the preferred technique for endothelial diseases and deep anterior lamellar keratoplasty the preferred technique for keratoconus, surpassing penetrating keratoplasty in 2013. Conclusion: Secondary endothelial failure is the top indication for performing a keratoplasty over the 12-year period. There was a shift from penetrating keratoplasty to endothelial keratoplasty performed for Fuchs endothelial corneal dystrophy and secondary endothelial failure, and to deep anterior lamellar keratoplasty, performed for keratoconus. This highlights an important shift in managing corneal diseases toward the application of selective and more conservative surgeries and changes in indications in corneal transplantation.